The Wealth and Asset Holdings of U.S.- Born and Foreign-Born Households: Evidence from SIPP Data - Deborah A. Cobb-Clark; Vincent A. Hildebrand (Institute for the Study of Labor (IZA), 2003)
SIPP data are used to analyze the wealth of the U.S. foreign-born population. We find that the median wealth level of U.S.-born couples is 2.3 times the median of foreign-born couples, while the median wealth level of U.S.-born singles is three times that of foreign-born singles. Further, there is a great deal of diversity in wealth within the immigrant population. Diversity in net worth manifests itself primarily in source-region differences, while entry-cohort is more closely related to portfolio choices. Established immigrants hold less and recent immigrants hold more financial wealth. An opposite pattern emerges with respect to real estate equity.
Keywords: G11; J10; J61; 330; immigrants; wealth; asset portfolios; Vermögensverteilung; Kapitalanlage; Einwanderung; Schätzung; Vereinigte Staaten